The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1126/scisignal.aaf6670
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP1 promotes amphetamine-induced motor behavior through a Rhes interaction network (“Rhesactome”) in the striatum

Abstract: The striatum of the brain coordinates motor function. Dopamine-related drugs may be therapeutic to patients with striatal neurodegeneration, such as Huntington's disease (HD) and Parkinson's disease (PD), but these drugs have unwanted side effects. In addition to stimulating the release of norepinephrine, amphetamines, which are used for narcolepsy and hyperactivity disorder (ADHD), trigger dopamine release in the striatum. The GTPase Ras homolog-enriched in the striatum (Rhes) inhibits dopaminergic signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 102 publications
6
71
0
Order By: Relevance
“…Briefly the cells were . Open field was conducted as described in our previous study (68). The inverted grip test was performed based on the Treat-NMD guidelines.…”
Section: Ribosome Isolation and In Vitro Binding Assaymentioning
confidence: 99%
“…Briefly the cells were . Open field was conducted as described in our previous study (68). The inverted grip test was performed based on the Treat-NMD guidelines.…”
Section: Ribosome Isolation and In Vitro Binding Assaymentioning
confidence: 99%
“…Moreover, RasGRP1 KO mice displayed no significant changes in basal motor behavior or coordination 16 , as shown in Supplementary Figs 3-5, which would not likely contribute much to the altered L-DOPA responses we observed.…”
Section: Introductionmentioning
confidence: 64%
“…Despite its high expression in brain regions, its role in neuronal functions remains unclear. Previously, we found that RasGRP1 interacts and acts as a GEF for Rhes and promotes amphetamine-induced hyperactivity via the striatal protein-protein complex known as Rhesactome 16 . Here, we have reported a major role for RasGRP1 in L-DOPA-induced dyskinesia and demonstrated that RasGRP1 is causally linked to L-DOPAinduced dyskinesia and robustly activates ERK and mTORC1 pathways in the striatum.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse STHdh Q7/Q7 (control), STHdh Q7/Q111 (HD-het), and STHdh Q111/Q111 (HD-homo) striatal neuronal cells (37). Striatal cells were cultured in growth medium containing Dulbecco's modified Eagle's medium high glucose (Thermo Fisher Scientific) with 10% fetal bovine serum (FBS), 1% penicillin-streptomycin at 33°C and 5% CO2, as described in our previous works (61,64,67).…”
Section: Cell Culturementioning
confidence: 99%
“…HRP-conjugated secondary antibodies (Jackson ImmunoResearchInc.) were probed to detect bound primary IgG with a chemiluminescence imager (Alpha Innotech) using enhanced chemiluminescence from WesternBright Quantum (Advansta)(67). The band intensities were quantified with ImageJ software (NIH).…”
mentioning
confidence: 99%